Comparative study of the retinal nerve fibre layer thickness performed with optical coherence tomography and GDx scanning laser polarimetry in patients with primary open-angle glaucoma - Wasyluk, Jaromir T. (International Scientific Literature, Inc., 2012)
BACKGROUND: We compared the parameters of retinal nerve fibre layer in patients with advanced glaucoma with the use of different OCT (Optical Coherence Tomograph) devices in relation to analogical measurements performed with GDx VCC (Nerve Fiber Analyzer with Variable Corneal Compensation) scanning laser polarimetry. MATERIAL/METHODS: Study subjects had advanced primary open-angle glaucoma, previously treated conservatively, diagnosed and confirmed by additional examinations (visual field, ophthalmoscopy of optic nerve, gonioscopy), A total of 10 patients were enrolled (9 women and 1 man), aged 18–70 years of age. Nineteen eyes with advanced glaucomatous neuropathy were examined. 1) Performing a threshold perimetry Octopus, G2 strategy and ophthalmoscopy of optic nerve to confirm the presence of advanced primary open-angle glaucoma; 2) performing a GDx VCC scanning laser polarimetry of retinal nerve fibre layer; 3) measuring the retinal nerve fibre layer thickness with 3 different optical coherence tomographs. RESULTS: The parameters of the retinal nerve fibre layer thickness are highly correlated between the GDx and OCT Stratus and 3D OCT-1000 devices in mean retinal nerve fibre layer thickness, retinal nerve fibre layer thickness in the upper sector, and correlation of NFI (GDx) with mean retinal nerve fibre layer thickness in OCT examinations. Absolute values of the retinal nerve fibre layer thickness (measured in μm) differ significantly between GDx and all OCT devices. CONCLUSIONS: Examination with OCT devices is a sensitive diagnostic method of glaucoma, with good correlation with the results of GDx scanning laser polarimetry of the patients.